South Papua Food Brigade Institution Development Strategy: The Path to Modernize Agriculture Towards Food Self-Sufficiency - Ananti Yekti; Nurhayati; Linda Tri Wira Astuti; Adi Prayoga; Kartika Ekasari Z (Jurnal Agrisistem: Seri Sosek dan Penyuluhan, 2026)
Food Brigade Institute was formed at the end of 2024 to support achieving national food self-sufficiency through the implementation of modern, efficient, sustainable, and technology-driven agricultural practices. This study aims to 1) identify and analyze internal and external factors that affect the institutional development of the Food Brigade in South Papua Province, and 2) formulate an alternative strategy for the institutional development of the Food Brigade in South Papua Province. The research was conducted from April to November 2025 in South Papua Province. A quantitative SWOT analysis was used in this study, starting with compiling the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices to determine the strategic position and formulate the development strategy. Primary data were collected through field observations, in-depth interviews, and focus group discussions, involving 17 key respondents. The results showed that the total score of IFE was -0.26 and the total score of EFE was 0.20, placing it in quadrant III, which is identical to the turnaround strategy. The formulation of the Food Brigade development strategy are 1) increasing the managerial capacity and digital literacy of all BP members through training 2) optimizing cooperation for cost efficiency, access to facilities, and risk mitigation 3) anticipating price fluctuations and climate change through planting system innovation, efficiency in the use of alsintan, and market information management 4) building a digital administration and governance system so that the Brigade Food institution is increasingly independent and bankable. This research can serve as a strategic basis for developing the Food Brigade's capacity to support agricultural modernization towards national food self-sufficiency.